2021
DOI: 10.1038/s41467-021-22660-9
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminus of an Ustilaginoidea virens Ser-Thr-rich glycosylphosphatidylinositol-anchored protein elicits plant immunity as a MAMP

Abstract: Many pathogens infect hosts through specific organs, such as Ustilaginoidea virens, which infects rice panicles. Here, we show that a microbe-associated molecular pattern (MAMP), Ser-Thr-rich Glycosyl-phosphatidyl-inositol-anchored protein (SGP1) from U. virens, induces immune responses in rice leaves but not panicles. SGP1 is widely distributed among fungi and acts as a proteinaceous, thermostable elicitor of BAK1-dependent defense responses in N. benthamiana. Plants specifically recognize a 22 amino acid pep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 68 publications
0
22
0
Order By: Relevance
“…In similar cases, cell death triggered by fungal endopolygalacturonases, the glycoside hydrolase 12 proteins, or elicitins is dependent on the Arabidopsis RLP AtRLP42, N. benthamiana RLP RXEG1, and Solanum microdontum RLP ELR (Zhang et al, 2013; Du et al, 2015; Wang et al, 2018). For many other elicitors, such as P. infestans apoplastic effector PC2, P. sojae effector AEP1, Zymoseptoria tritici effectors Zt9, Zt11, and Zt12 and Ustilaginoidea virens effector SGP1, although the corresponding immune receptors have not yet been identified, cell death activation has been shown to be reliant on membrane‐localized RLK BAK1 and/or SOBIR1 (Kettles et al, 2017; Song et al, 2021; Wang et al, 2021; Xu et al, 2021). One exception is Nep1‐like proteins (NLPs), for which cell death is activated by cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…In similar cases, cell death triggered by fungal endopolygalacturonases, the glycoside hydrolase 12 proteins, or elicitins is dependent on the Arabidopsis RLP AtRLP42, N. benthamiana RLP RXEG1, and Solanum microdontum RLP ELR (Zhang et al, 2013; Du et al, 2015; Wang et al, 2018). For many other elicitors, such as P. infestans apoplastic effector PC2, P. sojae effector AEP1, Zymoseptoria tritici effectors Zt9, Zt11, and Zt12 and Ustilaginoidea virens effector SGP1, although the corresponding immune receptors have not yet been identified, cell death activation has been shown to be reliant on membrane‐localized RLK BAK1 and/or SOBIR1 (Kettles et al, 2017; Song et al, 2021; Wang et al, 2021; Xu et al, 2021). One exception is Nep1‐like proteins (NLPs), for which cell death is activated by cytotoxic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that GPI-anchored proteins from fungal plant pathogens, such as Colletotrichum graminicola and M. oryzae , are essential for fungal cell wall integrity and fungal pathogenicity [ 61 , 62 ]. A recent study showed that a Ser-Thr-rich GPI-anchored protein (SGP1) from Ustilaginoidea virens , the causal agent of rice false smut, is required for U. virens pathogenicity and is also a fungal PAMP triggering PTI immunity [ 63 ]. SGP1 is widely distributed among fungi and its homologues from many fungi can also trigger PTI immune responses [ 63 ].…”
Section: Classification Of Fungal Elicitorsmentioning
confidence: 99%
“…A recent study showed that a Ser-Thr-rich GPI-anchored protein (SGP1) from Ustilaginoidea virens , the causal agent of rice false smut, is required for U. virens pathogenicity and is also a fungal PAMP triggering PTI immunity [ 63 ]. SGP1 is widely distributed among fungi and its homologues from many fungi can also trigger PTI immune responses [ 63 ]. Moreover, SGP1 treatment in N. benthamiana and rice significantly improved plant resistance to multiple fungal and bacterial pathogens [ 63 ], indicating good prospects of SGP1 elicitor in plant disease control.…”
Section: Classification Of Fungal Elicitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genomic analyses of U. virens suggested that U. virens encodes at least 628 potential secreted proteins, of which 193 are putative effectors (Zhang et al ., 2014). Among them, several effectors inhibit cell death or pattern‐triggered immunity in plants, including UvBI1, UvSGP1, UvSCRE1 and UvSCRE2 (UV_1261) (Fang et al ., 2016, 2019; Xie et al ., 2019; Zhang et al ., 2020; Song et al ., 2021), but their host targets and virulence mechanisms are unknown.…”
Section: Introductionmentioning
confidence: 99%